Hysteresis current controller for a general n‐level inverter fed drive with online current error boundary computation and nearly constant switching frequency. Issue 8 (1st September 2013) - Dey, Anubrata; Azeez, Najath Abdul; Mathew, Kallarackal; Gopakumar, Kumarukattan Nair; Kazmierkowski, Marian P.
Abstract : A space vector‐based hysteresis current controller for any general n ‐level three phase inverter fed induction motor drive is proposed in this study. It offers fast dynamics, inherent overload protection and low harmonic distortion for the phase voltages and currents. The controller performs online current error boundary calculations and a nearly constant switching frequency is obtained throughout the linear modulation range. The proposed scheme uses only the adjacent voltage vectors of the present sector, similar to space vector pulse‐width modulation and exhibits fast dynamic behaviour under different transient conditions. The steps involved in the boundary calculation include the estimation of phase voltages from the current ripple, computation of switching time and voltage error vectors. Experimental results are given to show the performance of the drive at various speeds, effect of sudden change of the load, acceleration, speed reversal and validate the proposed advantages.